A qualitative study exploring barriers and facilitators to establishing nurse-led, multidisciplinary psychological care for trauma patients: experiences from doctors and nurses - Yanan Leng; Ying Wu; Zonghua Wang; Xiaoping Zhou; Jianmei Liao (BMC Nursing, 2022)
Abstract Background Trauma patients are often in a state of psychological stress, experiencing helplessness, sadness, frustration, irritation, avoidance, irritability and other adverse emotions. Doctors and nurses are at the forefront of caring trauma patients and they play a crucial role in psychological supports and mental health care. However, few qualitative studies had based on the framework of the Theory of Planned Behavior (TPB) to explore the experiences in providing psychological care for trauma patients. We examined attitudinal, normative, and control beliefs underpinning medical staffs’ decisions to perform psychological care. Method A qualitative study of in-depth semi-structured interviews was conducted among 14 doctors and nurses engaging in trauma care. The participants came from six tertiary hospitals in Chongqing, China. Data analysis was performed using the approach of Colaizzi. According to the framework of TPB, the researchers identified and summarized the themes. Results Important advantages (mutual trust, patients' adherence and recovery), disadvantages (workload, short-term ineffective, practice unconfidently), referents (supportive: managers, patients, kinsfolk, nursing culture; unsupportive: some colleagues and patients), barriers (insufficient time or energy, resources situations), and facilitators (access to psychologist, training/education, reminders) were identified. Some demands, such as training diversity, multidisciplinary cooperation and families' support, reflected by doctors and nurses were important for them to carry out psychological care. Conclusion According to the TPB, this article explored the internal and external promotion and hindrance factors that affecting the intentions and behaviors of doctors and nurses in implementing psychological care for trauma patients. We also focused on the experience and demands of health professionals in conducting psychological care, which could provide references for managers to formulate corresponding psychological care procedures and norms.